Inmigración y escuela: un análisis sociométrico de la competencia social infantil percibida - Pizzinato, Adolfo (2022)
This research illustrates how immigrant and non-immigrant children differentiate themselves from their peers in the area of social competence, in schools in Porto Alegre (Brazil). After translation, adaptation and a reliability analysis of the instrument (Revised Class Play), it was applied on 32 immigrant children from different countries, who were living and studying in regular classes, together with their classmates (543, making a total of 575 participants). Also, a socio-demographic character identification was carried out among the participants to determine the groups’ profile. The data obtained indicates a perception that the immigrant children were more isolated, less aggressive and less sociable than their non-immigrant peers. This data contrasts with the perception of sociability that the immigrant children had about themselves.